Communication and skill - Vanpatten, Bill ([Place of publication not identifed] : Taylor & Francis, 2018)
In this module on communication, the reader explores the nature and consequences of a particular definition of communication: the expression and interpretation of meaning in a given context. Special attention is given to context (i.e., physical setting, participants, purpose of communication) and how these impact how we think about communication in language classrooms.
Communication and Skill
Communication and skill /, Communication
Keywords: LANGUAGE AND LANGUAGES -- STUDY AND TEACHING